2016
DOI: 10.1007/s40620-016-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring alloimmune response in kidney transplantation

Abstract: Currently, immunosuppressive therapy in kidney transplant recipients is generally performed by protocols and adjusted according to functional or histological evaluation of the allograft and/or signs of drug toxicity or infection. As a result, a large fraction of patients are likely to receive too much or too little immunosuppression, exposing them to higher rates of infection, malignancy and drug toxicity, or increased risk of acute and chronic graft injury from rejection, respectively. Developing reliable bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 110 publications
1
7
0
2
Order By: Relevance
“…AR in kidney transplantation is generally considered as an alloimmune response process involving networks of interacting cells throughout the body [ 22 ]. Our BP analysis showed that the mechanism of AR was primarily focused on immune process, and this finding is consistent with previous studies [ 6 , 23 ]. Then the CC ontology indicated that most of DEGs were membrane structures, such as proteins on integral component of membrane and plasma membrane.…”
Section: Discussionsupporting
confidence: 93%
“…AR in kidney transplantation is generally considered as an alloimmune response process involving networks of interacting cells throughout the body [ 22 ]. Our BP analysis showed that the mechanism of AR was primarily focused on immune process, and this finding is consistent with previous studies [ 6 , 23 ]. Then the CC ontology indicated that most of DEGs were membrane structures, such as proteins on integral component of membrane and plasma membrane.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the ability to quantify donor‐specific memory B cells in the clinical setting is critically needed, and a number of assays are currently being developed (reviewed in Ref. 40 ). Notably, the ability to quantify the frequency of all circulating memory B cells on the basis of the expression of CD27 and other markers, in pre‐ and posttransplant patients, represents a feasible approach but it is suboptimal, and an assay that quantifies the frequency of donor‐specific memory B cells will optimally identify patients with the potential of mounting a recall DSA response.…”
Section: Immunobiology Of Memory B Cellsmentioning
confidence: 99%
“…La implementación de un protocolo de seguimiento del paciente con trasplante renal basado en criterios inmunológicos podría constituir una herramienta para la detección temprana del rechazo mediado por anticuerpos y, en consecuencia, para la implementación de estrategias de manejo que prevengan o demoren al máximo la aparición del rechazo crónico o la pérdida del órgano trasplantado 13 , 16 , 17 .…”
Section: El Daño Del Injerto Ocurre Mucho Tiempo Antes Del Diagnósticunclassified